Incidencia y medidas alternativas de control para el moko (Ralstonia solanacearum) del banano en el Ecuador - AGUIRRE CHERREZ, JUAN CARLOS (2023)
Bananas (Musa. AAA) are grown in all tropical regions and are essential to the economies of many developing countries. The banana sector in Ecuador distributes more than 165,080 hectares, with a productivity of 6,023,390 tons. This is the most exported fresh fruit in the world in terms of volume and value. The bacterial moko, caused by the bacterium R solanacearum race 2. It is a gram-negative, rod-shaped bacterium, 0.5 to 0.7 microns in size x 1 to 2 um, mobile, with one to four strains of flagella, which vary according to the type of colony and the age of the crop. Depending on the variety used, the disease can be more severe, with the square plantain being the most vulnerable. The R. solanacearum bacterium represents a high potential pest threat in Ecuador due to the ease of distribution and popularity of different mechanisms, pathophysiological variations, management complexity and factors, a decisive factor in the reduction of commercial banana production in Ecuador, taking into account that moko can destroy up to 100% of the plantations where they occur. Banana Moko is considered one of the most important flowering plant conservation detriments to Musaceae. The R. solanacearum race 2 bacterium is present in countries in Africa, Southeast Asia, Central and South America, the Caribbean, Florida, and the European Union. Through various identification processes of this pathogen, the elimination of thousands of hectares of bananas in Latin America has been recorded. Pathogens enter host plants by natural or mechanical wounds. Control of Moko disease is limited, due to the absence of effective management technologies and banana plant varieties resistant to R. solanacearum disease. Sodium hypochlorite (3.5%) | 20% | 200ml/liter | (Blomme, G. et al, 2017) Quaternary Ammonium (20%) | 1200ppm | 6ml/liter. Inject 20% glyphosate solution into the pseudostem part (480 g/l product concentration) in a spiral fashion for all plants in that area using a graduated syringe.